2020
DOI: 10.1002/iid3.374
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hydroxychloroquine for treatment or prevention of SARS‐CoV‐2 infection: A rapid systematic review and meta‐analysis of randomized clinical trials

Abstract: Introduction Hydroxycloroquine (HCQ) has been extensively studied for treatment and prevention of coronavirus diseases 2019 (COVID‐19) from the start of the pandemic. Conflicting evidence about its usefulness has begun to accrue. Methods In the face of controversial results about clinical efficacy of HCQ, we performed a rapid systematic review to assess its safety in the framework of COVID‐19 randomized clinical trials. Results Five studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…18,19 However, later on, the use of HCQ in Covid-19 was abandoned and halted due to lack of efficacy and increased risk of toxicity like QT prolongation and cardiotoxicity, especially when combined with other QT-prolonging drugs as AZM. [20][21][22][23] Some cohort studies have reported beneficial outcomes using AZM, 24,25 while others could not confirm its efficacy. 26,27 Here, we conducted a systematic review and meta-analysis on randomized controlled trials to evaluate the safety and efficacy of AZM in treating Covid-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, later on, the use of HCQ in Covid-19 was abandoned and halted due to lack of efficacy and increased risk of toxicity like QT prolongation and cardiotoxicity, especially when combined with other QT-prolonging drugs as AZM. [20][21][22][23] Some cohort studies have reported beneficial outcomes using AZM, 24,25 while others could not confirm its efficacy. 26,27 Here, we conducted a systematic review and meta-analysis on randomized controlled trials to evaluate the safety and efficacy of AZM in treating Covid-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the African countries most affected by COVID-19 on June 4, 2020 are South Africa (37,525 cases and 792 deaths), Algeria (9,733 cases and 673 deaths) and Egypt (28,615 cases and 1,088 deaths), which belong to the countries historically less affected by malaria (7). This has been reported to be due to prophylaxis with chloroquine and hydroxychloroquine, which however have shown limited efficacy in COVID-19 (8). Furthermore, a recent publication confirmed a lower risk of COVID-19 in malariaendemic areas and, albeit with an underlying mechanism that has yet to be investigated, they identified shared immunodominant epitopes between SARS-CoV-2 and P. falciparum antigens (9).…”
Section: Introductionmentioning
confidence: 99%
“…The other side of the coin is that in mild COVID-19 patients or in a prophylactic setting, immunosuppression by HCQ could have a detrimental effect, since an efficient virus-specific anti-SARS-CoV-2 response depends on a robust antiviral innate immune response. We argue that ultimately the clinical effect of HCQ treatment in COVID-19 depends on the balance between inhibition of viral replication, immunosuppression, and off-target side effects (which have been extensively evaluated recently, within and outside the setting of COVID-19 treatment or prevention, in [61,62], and are as such not the topic of this article). The outcome of this balance is probably dependent on disease stage and disease severity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%